Contemporary surgical strategies for pediatric laryngotracheal stenosis: a comprehensive review - Oscé, Hanne; Meulemans, Jeroen; Hens, Greet (Frontiers in Pediatrics, 2025)
BackgroundPediatric laryngotracheal stenosis (LTS) presents a complex and heterogeneous clinical challenge, requiring individualized surgical approaches to restore airway patency and function. Depending on stenosis severity, anatomical site, and comorbidities, a range of surgical techniques—including laryngotracheal reconstruction (LTR), partial cricotracheal resection (PCTR), extended PCTR, and endoscopic posterior cricoid split with rib grafting (EPCS/RG)—may be employed.MethodsThis narrative review synthesizes current surgical strategies for pediatric LTS based on current literature, highlighting their indications, operative considerations, and reported outcomes. Key factors affecting surgical success, such as patient selection and perioperative management, are discussed.ResultsSingle-stage LTR is favored in healthy children with moderate SGS, while PCTR offers superior outcomes in severe or recurrent cases. EPCS/RG represents a minimally invasive alternative for LTR in selected cases with posterior glottic stenosis. Decannulation rates generally exceed 85% in carefully selected patients, though voice and swallowing outcomes vary by technique.ConclusionOptimal management of pediatric LTS requires a multidisciplinary, tailored approach. Continued focus on long-term functional outcomes, technical innovations, and multicenter collaboration will further improve patient care.